IMPROVING THE TENTH GRADE STUDENTS’ READING SKILLS BY USING MIND MAPPING TECHNIQUE - Mardayani Mardayani; Magdad Hatim (ELTE Journal (English Languange Teaching and Education), 2020)
This study was a classroom action research which concerned with the inquiry on how mind mapping technique could improve the reading skill of the tenth-grade students’ of State Senior high School 1 of Ujanmas. This research was conducted into three cycles (cycles 1,2, and 3) and the preliminary stage was initiated before the study was conducted. Each cycle had four steps: plan, action, observation, and reflection. The subjects of the research were thirty-five tenth-grade students. The technique for collecting qualitative data employed was an observation, to know the improvement of teaching and learning activities, whereas quantitative data were obtained through a reading test. The research result showed that (1) mind mapping technique could improve the students reading skill, (2) mind mapping technique could enhance students’ motivation in the teaching and learning process, (3) mind mapping technique could increase students’ attention to understand and students were encouraged in asking and answering a question. In conclusion, the tenth-grade students’ reading skills could be improved by using the mind mapping technique.